Translating Harry Potter for a Sepedi audience - Sehlola, Patrick Sekgathi (My University, 2011)
This study explores the translation of the first Harry Potter book into Sepedi. Selected passages are chosen for translation and the strategies adopted are examined with regard to the rendition of specific cultural elements, namely, food, proper names, humour, forms of address and the transport system for the Sepedi audience. Secondly, it answers the question of which elements of the story could be regarded as effective in the target culture, particularly given that it is characterised by witchcraft and wizardry. One of the subsidiary aims of this study is to introduce a genre of fantasy for children in the target culture through translation, and to investigate whether this could encourage a culture of reading among young children within the African culture, and the Sepedi culture in particular. Currently, this type of genre does not exist in any translation for the target audience. Therefore, Harry Potter with its history of changing and shaping the culture of reading internationally was an obvious choice for this research.
M.A. Faculty of Humanties, University of the Wiwatersrand, 2011